Analisis Sistem dan Kebijakan Pendidikan Islam tentang Penggunaan Dana Bantuan Operasional Sekolah (BOS) - Refnawati, Refnawati; Yovica, Alia; Octavia, Lidya Fransiska; Rahmi, Sri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article aims to analyze the Islamic education system and policy on the use of BOS funds. This study uses a literature study method with a systematic approach to identify and analyze relevant sources related to the research focus. The data source is taken from scientific journals, books, and academic publications published in the last 10 years, using an online database, namely Google Scholar. The collected data is analyzed qualitatively to identify the main themes and trends in related research. The results of the analysis show that the use of BOS funds is intended for all routine school operating costs, while construction costs do not come from BOS. Abuse in the management of BOS funds is found in several regions, the most frequent cases are the inflating of the number of students, misuse of funds, and even falsification of data and news which often include newspapers about the misappropriation of BOS funds. This can also be triggered by the current system, weak supervision and lack of community participation, thus causing the purpose of the BOS subsidy itself to be less and tend to reduce its usefulness. For this reason, preventive actions are needed from every institution and element of this nation for the progress and effective management of BOS funds